Pengolahan Air Limbah Laundry dengan Presipitasi Selektif Hidroksiapatit dan Reaktor Biofilm Moving Bed - Iva Rustanti Eri Wardoyo; Darjati Darjati; Khambali Khambali; Elmi Sumiyarsono (Jurnal Sehat Mandiri, 2024)
Inorganic phosphate compounds (P2O4) can cause acute poisoning if inhaled in large quantities. The aim was to remove inorganic phosphate compounds (P2O4) from laundry wastewater. This research was carried out in the Poltekkes Surabaya laboratory in January 2024. This research was pure experiment. The tools used was an MBBR reactor, with a capacity of 1 M3/day with inlet-outlet pipes, sample port, mud disposal pipe. Monitoring parameters are temperature, pH, ORP, COD, total N and P2O4. Biomass analysis of the biofilm media was carried out gravimetically. The waste water used comes from household laundry. The findings showed that the reduction in MBBR organic compounds in the system was around 63-78%, while in the denitrification process was 48-52%. The average concentration of organic substances taken at the outlet was less than 100 mg/L, the decrease in total N concentration was around 43-55%, the P2O4 concentration taken at outlet was 0.78-0.86 mg/L. The average reduction in P2O4 was 19%, while the average reduction in the denitrification process was 55%. In conclusion, the use of the MBBR system can be effective in processing organic compounds and reducing the concentration of Total N and P2O4 in wastewater. Suggestions for further research are to be able to utilize the MBBR system for a longer period of time so that we can see the saturation point of the tool in treating waste water.